How to draw the line: A note on local market definition - Dieter Pennerstorfer; Biliana Yontcheva (Johannes Kepler University of Linz, Department of Economics, 2019)
This article presents a novel method of market delineation, which generates virtually isolated residential clusters using data on the spatial distribution of population. The performance of this approach is evaluated by contrasting it with traditional delineation techniques based on municipal boundaries. The estimation of simple entry models for five industries shows that markets defined using micro-level residence information perform better in terms of reducing cross-border spatial spillovers and predicting the equilibrium number of firms on the market more accurately. Additionally, the estimated entry threshold ratios using this method successfully reflect our expectations based on ex-ante knowledge about the investigated industries.
Keywords: L13; L11; R32; 330; market definition; entry models; spatial competition